Peran Koperasi Universiti Kebangsaan Berhad Malaysia dalam Mendorong Kesejahteraan Ekonomi Anggota - Marlina, Serly; Agustina, Tri; Rahmat, Rasyid; Purbo Suseno, Gijanto (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
Cooperatives are business entities that play a crucial role in developing the economic potential and capabilities of their members, with the goal of improving their welfare. The Universiti Kebangsaan (UNIKEB Berhad) Cooperative in Malaysia is one such multi-purpose cooperative that has successfully fulfilled its role despite facing various business challenges. This cooperative, which primarily comprises academic staff and students, has been operating for over five decades and manages business units that include real estate (property leasing), retail, financing, gas station management, and Ar-Rahnu (pawn services). This research aims to analyze the role and performance of UNIKEB Berhad Cooperative in promoting the economic sustainability of its members. The research employs a qualitative approach, utilizing secondary data from UNIKEB Berhad as well as interviews and discussions with the management, supervisors, and members of the cooperative. The findings indicate that UNIKEB Berhad Cooperative has successfully acted as a platform to promote the economic welfare of its members, reflected in its operational growth and stability over more than five decades. The cooperative has also managed to analyze the business challenges it faces, including declining member participation, liquidity constraints, dependence on external funding, and decreasing dividends or profit-sharing. Based on this analysis, UNIKEB Berhad Cooperative has effectively evaluated and designed three strategies to promote the long-term economic sustainability of its members, focusing on funding structure, governance, and member commitment. These findings provide important implications for cooperatives facing similar business challenges in formulating appropriate strategies.